Safety and Dose-Dependent Effects of Echinacea for the Treatment of Acute Cold Episodes in Children: A Multicenter, Randomized, Open-Label Clinical Trial - Ramon Weishaupt; Arnold Bächler; Simon Feldhaus; Günter Lang; Peter Klein; Roland Schoop (MDPI AG, 2020)
Background: Due to the frequency and severity of cold symptoms in children, and the risk of associated complications, effective treatments are urgently needed. Here we evaluated the safety profile and treatment benefits of Echinacea in children with acute cold and flu symptoms. Methods: A total of 79 children (4-12 years) were randomized to a treatment regimen of three or five times daily Echinaforce Junior tablets (total of 1200 or 2000 mg Echinacea extract, EFJ) for the prospective treatment of upcoming cold and flu episodes at first signs. Parents recorded respiratory symptoms daily during episodes in their child and physicians and parents subjectively rated tolerability. Results: EFJ was used to treat 130 cold episodes in 68 children and was very well tolerated by more than 96% positive physician's ratings. EFJ-treated cold episodes lasted 7.5 days on average, with nine out of 10 episodes being fully resolved after 10 days. Five EFJ tablets daily reduced the average episode duration by up to 1.7 days (p < 0.02) in comparison to three EFJ tablets daily regimen. Effective symptom resolution finally contributed to a low antibiotic prescription rate in this study of 4.6%. Conclusions: EFJ tablets present a valuable option for the treatment of acute cold episodes in children showing a wide safety margin and increased therapeutic benefits at five tablets daily.